Empowering Women Through Education, Health and Employment - Palaniappan, A.; Aniyan, Anish C. (Prabandhan: Indian Journal of Management, 2010)
The constitution grants equal rights to men and women. Yet, the reality is that women’s lives are still shaped by customs and traditions that work against them. Daughters are viewed as less valuable than sons. Girls are taught to believe that they are less important than boys. In India, for the first time, women are recognized not just as equal citizens but as agents of economic and social growth (Eleventh Plan). For growth to be truly inclusive, we have to ensure their protection, well being, development, empowerment and participation. We have to ensure the survival, protection and all -round development of women of all ages, communities and economic groups. To end the multifaceted exclusions and discriminations faced by women and to ensure that every woman in the country is able to develop her full potential and share the benefits of economic growth and prosperity depends on our ability to adopt a participatory approach that empowers women and makes them partners in their own development. We can achieve this by providing the basic necessities like good education, health and employment. Various necessary measures have to be taken to strengthen women through education, health and employment. All these measures can help to improve the status of women. Women empowerment requires the removal of all the above disabilities and the restoration of equal rights to women in all economic and social activities -only such a measure will enable them to contribute towards faster growth and development of the economy. In this paper, we discuss about various measures that have been adopted by the Government and NGO’s for empowering women and some suggestions to boost up the on going reform measures to empower women.